Cochlear labyrinth volume in Krapina Neandertals. Issue 90 (January 2016) - Beals, Michaela E.; Frayer, David W.; Radovčić, Jakov; Hill, Cheryl A.
Abstract: Research with extant primate taxa suggests that cochlear labyrinth volume is functionally related to the range of audible frequencies. Specifically, cochlear volume is negatively correlated with both the high and low frequency limits of hearing so that the smaller the cochlea, the higher the normal range of audible frequencies. The close anatomical relationship between the membranous cochlea and the bony cochlear labyrinth allows for the determination of cochlear size from fossil specimens. This study compares Krapina Neandertal cochlear volumes to extant taxa cochlear volumes. Cochlear volumes were acquired from high-resolution computed tomography scans of temporal bones of Krapina Neandertals, chimpanzees, gorillas, and modern humans. We find that Krapina Neandertals' cochlear volumes are similar to modern Homo sapiens and are significantly larger than chimpanzee and gorilla cochlear volumes. The measured cochlear volume in Krapina Neandertals suggests they had a range of audible frequencies similar to the modern human range.